Response of round-hole tubes submitted to pure bending creep and pure bending relaxation - Kuo-Long Lee; Bo-You Liu; Wen-Fung Pan (Advances in Mechanical Engineering, 2021)
This paper presents experimental study on the response of 6061-T6 aluminum alloy round-hole tubes with five different hole diameters of 2, 4, 6, 8, and 10 mm and four different diameter-to-thickness ratios of 30, 40, 50, and 60 submitted to pure bending creep and pure bending relaxation. Pure bending creep or relaxation is defined as bending the tube to the required moment or curvature and maintaining that moment or curvature for a period of time. The experimental results of pure bending creep show that the curvature increases with time. In addition, larger holding moment, diameter-to-thickness ratio, or hole diameter results in larger creep curvature. As the curvature continues to increase, the round-hole tube eventually breaks. The experimental results of pure bending relaxation show that the relaxation moment decreases sharply with time and tends to a stable value. In addition, larger holding curvature, diameter-to-thickness ratio, or hole diameter results in larger drop of the relaxation moment. Due to fixed curvature, the round-hole tube does not break. Finally, formulas proposed by the research team of Pan et al. were respectively improved to simulate the creep curvature-time relationship for pure bending creep in the initial and the secondary stages and the relaxation moment-time for pure bending relaxation. After comparing with the experimental results, it is found that theoretical analysis can reproduce the experimental results reasonably.